A Review on Lignin‐Based Phenolic Resin Adhesive. Issue 4 (7th January 2022) - Gong, Xiaoyu; Meng, Yi; Lu, Jie; Tao, Yehan; Cheng, Yi; Wang, Haisong
Abstract: Replacing petroleum‐based chemicals with biomass‐based alternatives is becoming more and more important for the development of a low‐carbon economy around the world. The latest life cycle assessment displayed that partially replacing phenol with biobased lignin in the process of synthesizing phenolic resin adhesives used in wood panels industry can remarkably reduce carbon emissions and negative environmental impact. The macromolecular structure of lignin is similar to that of phenolic resin and the basic structure unit is similar to that of the phenol, thus endowing it with the potential to substitute phenol and reduce the release of formaldehyde in the preparation process of phenolic resin. Importantly, the lignin‐based adhesive exhibits improved performance and reduced cost compared with the petroleum‐based adhesive due to the reduced adding amount of petroleum‐based volatile components. However, the intrinsic large steric hindrance, structural heterogeneity, and low activity of the natural lignin limit its further application in the adhesive. Many researchers have developed the activation methods such as physical modification, chemical modification, and biological modification to overcome these issues. The different modification of the lignin and their application in the adhesive area are mainly summarized here. Besides, the modification methods and the curing mechanism are also discussed. Abstract : The different modifications of lignin and their application in adhesives are summarized here. On the basis of summarizing structural characteristics of lignin and the life cycle assessment of lignin phenol‐formaldehyde (LPF) adhesives, research gaps and outlooks are elucidated to brighten LPF's future.